Punching of reinforced concrete flat slabs – Rational use of high strength concrete. (1st March 2020) - Inácio, Micael M.G.; Lapi, Massimo; Pinho Ramos, Antonio
Highlights: The partial use of High Strength Concrete (HSC) to increase the punching capacity is shown. The use of HSC in compressive zone is much more efficient than that in tensile zone. Experimental and analytical results support the use of HSC limited to a thin layer in compressive zone near the column. The use of HSC in the compressive zone gives almost the same punching strength of a slab entirely casted in HSC. The rational use of HSC leads to a more economical and sustainable solution. Abstract: This paper deals with punching of reinforced high strength concrete (HSC) flat slabs. Despite the use of HSC increased significantly in the last years, the experimental research on punching behavior of HSC slabs is still limited. Furthermore, most of this past research adopted concrete compressive strength lower than 90 MPa. In a previous work by this research group three specimens with concrete compressive strength around 120 MPa and one with normal strength concrete (NSC) were tested. The present work represents the continuation of the previous activity and it is focused on the rational use of HSC. Four specimens with HSC and one of NSC were tested under monotonic vertical loading. The HSC was placed only in the slab-column connection region and it was limited to a thin layer in the compressive zone, in order to have a more economical and sustainable solution. This rational use of the HSC showed excellent results in terms of punching strength. Limiting the HSC to a thin layer in the compressive zone resulted in an almost equal punching strength to that obtained with the slab entirely casted in HSC.